Left–right differences in the proximal femur's strength of post-menopausal women: a multicentric finite element study. Issue 4 (April 2016) - Taddei, F.; Falcinelli, C.; Balistreri, L.; Henys, P.; Baruffaldi, F.; Sigurdsson, S.; Gudnason, V.; Harris, T.; Dietzel, R.; Armbrecht, G.; Boutroy, S.; Schileo, E.
Abstract Summary The strength of both femurs was estimated in 198 post-menopausal women through subject-specific finite element models. Important random differences between contralateral femurs were found in a significant number of subjects, pointing to the usefulness of further studies to understand if strength-based classification of patients at risk of fracture can be affected by laterality issues. Introduction Significant, although small, differences exist in mineral density and anatomy of contralateral proximal femurs. These differences, and their combined effect, may result in a side difference in femurs' strength. However, this has never been tested on a large sample of a homogenous population. Methods The strength of both femurs was estimated in 198 post-menopausal women through CT-derived finite element models, built using a validated procedure, in sideways fall conditions. The impact of the resulting asymmetry on the classification of subjects at risk of fracture was analysed. Results The small difference observed between sides (the right femur on average 4 % stronger than the left) was statistically significant but mechanically negligible. In contrast, higher random differences (absolute difference between sides with respect to mean value) were found: on average close to 15 % (compared to 9.2 % for areal bone mineral density (aBMD) alone), with high scatter among the subjects. When using a threshold-based classification, the right and left femurs were discordant up to over 20 % of cases (K always lower than 0.60) but the left femur was concordant (meanK = 0.84) with the minimum strength between right and left. Conclusion Considering both femurs may be important when trying to classify subjects at risk of failure with strength estimates. Future studies including fracture assessment would be necessary to quantify the real impact.